Autophagy-Enhancing Properties of Hedyotis diffusa Extracts in HaCaT Keratinocytes: Potential as an Anti-Photoaging Cosmetic Ingredient - Qiwen Zheng; Xiangji Jin; Trang Thi Minh Nguyen; Eun-Ji Yi; Se-Jig Park; Gyeong-Seon Yi; Su-Jin Yang; Tae-Hoo Yi (Molecules)
The decline in autophagy disrupts homeostasis in skin cells, leading to oxidative stress, energy deficiency, and inflammation—all key contributors to skin photoaging. Consequently, activating autophagy has become a focal strategy for delaying skin photoaging. Natural plants are rich in functional molecules and widely used in the development of anti-photoaging cosmetics. Hedyotis diffusa (HD), as a medicinal plant, is renowned for its anti-inflammatory and anticancer properties; however, its effects on skin photoaging remain unclear. This study investigates HD’s potential to counteract skin photoaging by restoring mitochondrial autophagy in keratinocytes. We used HPLC to detect the main chemical components in HD and, using a UVB-induced photoaging model in HaCaT keratinocytes, examined the effects of HD on reactive oxygen species (ROS) levels, Ca2+ concentration, mitochondrial membrane potential (MMP), apoptosis, and the cell cycle. Cellular respiration was further evaluated with the Seahorse XFp Analyzer, and RT-PCR and Western blotting were used to analyze the impact of HD on mitochondrial autophagy-related gene expression and signaling pathways. Our findings indicate that HD promotes autophagy by modulating the PI3K/AKT/mTOR and PINK/PARK2 pathways, which stabilizes mitochondrial quality, maintains MMP and Ca2+ balance, and reduces cytochrome c release. These effects relieve cell cycle arrest and prevent apoptosis associated with an increased BAX/BCL-2 ratio. Thus, HD holds promise as an effective anti-photoaging ingredient with potential applications in the development of cosmetic products.